Analysis of Halal Food Product Certification in Micro and Small Enterprises (MSEs) in Increasing Product Sales Value in Bone Regency - Samsidar; Muslimin Kara; Jamaluddin; Abdul Wahab; Kamaruddin (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2025)
This research aims to determine the relationship between halal food product certificates in micro and small enterprises and the increase in the sales value of these products in Bone Regency. This study used qualitative research with data collection techniques, interviews, documentation, and literature observation. The research approach used in this research is phenomenology. To increase the selling value of the product, it must show product quality that refers to Islam, of course, food products that are halal certified. Halal certificates can play an important role in proving to consumers that the product meets the requirements so that consumers feel safe in consuming the product.